Passive restoration of subtropical grassland after abandonment of cultivation. Issue 1 (13th November 2015) - Fensham, Rod J.; Butler, Don W.; Fairfax, Russell J.; Quintin, Amy R.; Dwyer, John M.
Summary: Passive restoration of grasslands after the abandonment of cultivation may be a viable restoration option where seed sources from remnant grasslands are available, and if the risk of deflected succession is low. Passive restoration of subtropical grassland in Queensland, Australia was evaluated along a chronosequence of abandoned cultivation (fallow) paddocks. Plant communities in fallow paddocks were compared with nearby remnant grassland. On average, species richness recovers after 60 years of abandonment and floristic composition shows affinities with nearby remnant grassland (Bray‐Curtis ˜ 0·6). The risk of deflected succession, such as dominance by exotic grasses, has apparently been low in this ecosystem. Annual grasses and forbs are rapid colonizers of the abandoned fields, and richness of perennial forbs exhibits near‐linear recovery. Perennial grasses are relatively slow to establish but all except two species have statistically insignificant differences in abundance between remnant grassland and fallow fields after 20 years. The perennial grasses that recover most rapidly in fallow paddocks have disseminules that are adorned with appendages for wind dispersal including the most important dominant grass, Dichanthium sericeum . The perennial grasses that are slowest to recover are probably less effective dispersers. Synthesis and applications . Passive restoration of grasslands after the abandonment of cultivation can be a viable contribution to grassland conservation where there is an adequate matrix of remnant grasslands in the vicinity of fallows, perennial exotic species do not monopolize fallows and the dominant native grasses are well dispersed.